Dimensionamiento de Un Sistema Fotovoltaico De Emergencia Para Los Cuatro Motores Del Sistema De Filtrado De Aire Continuo En La Planta De Alimentos GIOMER - Melo Torres, Sergio Nicolás (Universidad Antonio Nariño, 2023)
The purpose of this project is to solve a problem at the GIOMER food plant. The plant has a set of motors that allow for the supply and extraction of air during a full day of work. In cases of unexpected power outages, a separate energy supply is needed to ensure he continuous operation of the system. To address this issue, an autonomous photovoltaic system is being designed to provide power to the motors in less than 15 minutes.